2016
DOI: 10.1111/jar.12319
|View full text |Cite
|
Sign up to set email alerts
|

Job Satisfaction, Quality of Work Life and Work Motivation in Employees with Intellectual Disability: A Systematic Review

Abstract: Stronger consideration of well-established theories and measures from organizational psychology would enhance future research. Findings indicate that high satisfaction ratings might result from lack of control over vocational decisions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
79
0
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 88 publications
(94 citation statements)
references
References 42 publications
2
79
0
3
Order By: Relevance
“…Word search terms relating to employment and health were collated by examining terms occurring in existing systematic reviews relating to employment and physical or mental health in the general population (Hergenrather et al, 2015a(Hergenrather et al, , 2015bModini et al, 2016) and other relevant literature reviews (Beyer & Robinson, 2009;Kocman & Weber, 2018;Lysaght, Cobigo, & Hamilton, 2012).…”
Section: Me Thodmentioning
confidence: 99%
See 1 more Smart Citation
“…Word search terms relating to employment and health were collated by examining terms occurring in existing systematic reviews relating to employment and physical or mental health in the general population (Hergenrather et al, 2015a(Hergenrather et al, , 2015bModini et al, 2016) and other relevant literature reviews (Beyer & Robinson, 2009;Kocman & Weber, 2018;Lysaght, Cobigo, & Hamilton, 2012).…”
Section: Me Thodmentioning
confidence: 99%
“…Subsequent studies have also found that people with intellectual disabilities in employment report better QoL (Memisevic, Hadzic, Zecic, & Mujkanovic, 2016) and that QoL is higher for those in open employment compared to sheltered employment (Kober & Eggleton, 2005). A more inclusive setting (e.g., competitive/integrated employment) is also generally associated with higher levels of job satisfaction for people with intellectual disabilities (Akkerman, Janssen, Kef, & Meininger, 2016;Kocman & Weber, 2018). Conversely, people with intellectual and developmental disabilities who lack productivity more broadly describe a significant void in their life due to the absence of both meaningful activity and social connections (Lysaght, Petner-Arrey, Howell-Moneta, & Cobigo, 2017).…”
mentioning
confidence: 97%
“…The high relevance of job satisfaction warrants the need of a well‐devised and tested best‐practice assessment instrument for job satisfaction for people with intellectual disability, both suited for research and for ongoing evaluation in sheltered workshops and supported employment. However, recent reviews on job satisfaction in this population (Akkerman, Janssen, Kef, & Meininger, ; Kocman & Weber, ) indicate a high variety of qualitative and quantitative instruments being used to assess job satisfaction in research so far. This heterogeneity of instruments is similar to job satisfaction research in the general population (Ferreira, ).…”
Section: Introductionmentioning
confidence: 99%
“…Quantitative approaches can be categorized into three distinctive groups (Kocman & Weber, ): studies applying questionnaires intended for the general population in their original version (e.g., Fornes, Rocco, & Rosenberg, ), adapted versions of questionnaires used in the general population (e.g., Melchiori & Church, ), and measures specifically designed for people with intellectual disability (e.g., Chiocchio & Frigon, ).…”
Section: Introductionmentioning
confidence: 99%
“…Also, aside from developing their work-related skills, effective vocational training has positive behavioral and social effects that result in increased quality of life of persons with IDD (Buntix and Schalock 2010;Timmons et al 2011). A further benefit of vocational training is that it offers the possibility of overcoming the problems resulting from poor qualifications in and little knowledge of modern technology, in as much as it emphasizes practical learning, corresponding to the adaptive skills available to the individuals (Kocman and Weber 2016).…”
Section: Introductionmentioning
confidence: 99%